An Assessment of the Growth Debate: A Comparison of Perspectives - Jeroen C.J.M. van den Bergh; Ruud A. de Mooij (Tinbergen Institute, 1997)
The debate on growth versus environment, including the more recent literature on sustainabledevelopment, is systematically evaluated in a stylized framework. Diffent perspectives on the conflictand relation between the economy, growth and the natural environment, have created a situationwhere people do not talk the same language. A conceptual framework is developed which allows toexplain main diffences between alternative perspectives. Five categories are distinguished, labelledas: the immaterialist, the pessimist, the technocrat, carpe diem and the optimist. Boththe conceptual framework and a set of characteristics (time horizon, ideology, prediction and policyimplication) are used to compare these perspectives. Primarily the choice of a time horizon and thesubjective evaluation of technical potential, the flexibility of social preferences and institutions, andthe stability and resilience of natural systems, explain differences between the perspectives. Sucha systematic confrontation is hoped to contribute to more consensus and understanding betweensupporters of alternative perspectives.
Keywords: 330; Umweltökonomik; Steady-State-Ökonomie; Theorie